Factors influencing local’s intention to dine in at Binjai Bistro, Ulek Beach Resort / Nurhhjayatul Asma Noor Din and Siti Asma Yaacob - Noor Din, Nurhhjayatul Asma; Yaacob, Siti Asma (2019)
This undergraduate project aims to explore the factors that influence local’s intention to dine in at Binjai Bistro and to explore which is the most significant factor that influence the local’s intention to dine in at Binjai Bistro, Ulek Beach Resort. In the research problem, the researcher highlighted that the issue of Binjai Bistro is the restaurant was lack of guests even in peak season or public holiday. Moreover, to attain the objectives of this research project, research questions are developed. Other than that, literature reviews are included in this research project as to provide better understanding towards the influential factors on local’s intention to dine in at Binjai Bistro as well as to provide justification towards the research frameworks. Primary data were collected through questionnaire for this research purposes and 223 sets of questionnaire were distributed to the target respondents which are local peoples from Sura area in Dungun. The data collected through the questionnaires are analyzed by using Statistical Package for Social Science (SPSS) version 25.0 and the findings obtained are discussed. In addition, major findings of this research project were discussed in order to determine what is the factor that influence local’s intention to dine in at Binjai Bistro as well as to identify which is the most significant factors that affect local’s intention to dine in at the restaurant. After this research, the researcher acknowledge that the factor of word-of-mouth is the most significant factor that influence the intention of local people in Dungun to dine in at Binjai Bistro.